Renoprotective Effects of Tanshinone IIA: A Literature Review - Zhengtao Chen; Haoyue Feng; Chuan Peng; Zehua Zhang; Qianghua Yuan; Hong Gao; Shiyun Tang; Chunguang Xie (Molecules, 2023)
The kidney is an important organ in the human body, with functions such as urine production, the excretion of metabolic waste, the regulation of water, electrolyte and acid–base balance and endocrine release. The morbidity and mortality of kidney diseases are increasing year by year worldwide, and they have become a serious public health problem. In recent years, natural products derived from fungi, plants and animals have become an important alternative source of treatment for kidney diseases because of their multiple pathways, multiple targets, safety, low toxicity and few side effects. Tanshinone IIA (Tan IIA) is a lipid-soluble diterpene quinone isolated from the Chinese herb Salvia miltiorrhiza, considered as a common drug for the treatment of cardiovascular diseases. As researchers around the world continue to explore its unknown biological activities, it has also been found to have a wide range of biological effects, such as anti-cancer, anti-oxidative stress, anti-inflammatory, anti-fibrotic, and hepatoprotective effects, among others. In recent years, many studies have elaborated on its renoprotective effects in various renal diseases, including diabetic nephropathy (DN), renal fibrosis (RF), uric acid nephropathy (UAN), renal cell carcinoma (RCC) and drug-induced kidney injury caused by cisplatin, vancomycin and acetaminophen (APAP). These effects imply that Tan IIA may be a promising drug to use against renal diseases. This article provides a comprehensive review of the pharmacological mechanisms of Tan IIA in the treatment of various renal diseases, and it provides some references for further research and clinical application of Tan IIA in renal diseases.